Suppose S is open and let p be a cluster point of ~ S . We can establish that.... Then p is contained in S . Since S is open, there exists a segment r containing p such that r...

1 Answers · Science & Mathematics · 22/10/2010

S x S is the set of pairs (x,y) such that x and y are in S and is called the Cartesian ( or direct) product of the set S ...

2 Answers · Science & Mathematics · 29/03/2012

Find cos( s +t) and cos( s -t)? Given : Cos s = -8/17 & cos t=-3/5 & s and t are in quadrant 3 Now cos( s ) = −8/17 sin( s ) =±√ {1−cos²( s )} =±√ {1−(−8/17)²}=±√ {1−64/289}=±√ {225/289...

1 Answers · Science & Mathematics · 03/05/2011

Let S ⊆ R with S ≠ ∅ and S is bounded below... S }. Proof: Strictly speaking we should show that -sup{- s : s ∈ S } exists. Let B be a lower ...

2 Answers · Science & Mathematics · 07/12/2010

This is a 1st order ODE in Y( s ). Rearranging (I assume you ve missed a + after the 1st...we have A = 1, B = 3. We can now integrate: int (4s + 2) / ( s ( s + 2) ) ds = int 1/ s + 3/( s +2) ds = ln( s ) + 3ln( s +2) + C ...

1 Answers · Science & Mathematics · 16/08/2008

asumming | S | = a and |T| = b and | S ∩ T| = c if they have no common member then c=0 if x belong to S U T it means case1) x belong to S only or case2) x...

4 Answers · Science & Mathematics · 18/09/2008

It s originally Save Our Souls but it s also used as ... Ships and Sink Or Swim . There s also rumors that it doesn t stand for anything, and was a mistake, however...

5 Answers · Education & Reference · 22/08/2008

**Ss**x**ss**. The seeded plant produces 2 gametes S and s in equal proportion, the seedless plant only s . They combine to give**Ss**and**ss**in a 1:1 ratio, so they will be 50% seeded and 50% seedless.2 Answers · Science & Mathematics · 14/11/2012

**Ss**x**ss**. The seeded plant produces 2 gametes S and s in equal proportion, the seedless plant only s . They combine to give**Ss**and**ss**in a 1:1 ratio, so they will be 50% seeded and 50% seedless.2 Answers · Science & Mathematics · 17/01/2017

s = e( s +p) = es + ep, so s - es = ep, and s (1-e) = ep, sp s = ep/(1-e)

6 Answers · Science & Mathematics · 28/08/2007